Electron and muon anomalous magnetic dipole moment in a 3-3-1 model - De Conto, G. [UNESP]; Pleitez, V. [UNESP] (Springer, 2017)
We calculate, in the context of a 3-3-1 model with heavy charged leptons, constraints on some parameters of the extra particles in the model by imposing that their contributions to both the electron and muon (g - 2) factors are in agreement with experimental data up to 1 sigma-3 sigma. In order to obtain realistic results we use some of the possible solutions of the left-and right-unitary matrices that diagonalize the lepton mass matrices, giving the observed lepton masses and at the same time allowing to accommodate the Pontecorvo-Maki-Nakagawa-Sakata (PMNS) mixing matrix. We show that, at least up to 1-loop order, in the particular range of the space parameter that we have explored, it is not possible to fit the observed electron and muon (g - 2) factors at the same time unless one of the extra leptons has a mass of the order of 20-40 GeVs and the energy scale of the 331 symmetry to be of around 60-80TeVs.
Keywords: Beyond Standard Model; Gauge Symmetry